(untitled) - Rosenzweig, Mark R (Sunderland, Mass., 2002)
Univ. of California, Berkeley. Textbook explores the biological bases of the ways in which bodily states and processes produce and control behavior and cognition, and the ways in which behavior, cognition, and the environment exert their influence on bodily systems. Includes icons, key terms, boxes, and a CD-ROM containing study aids. Previous edition: c1999. Colorful format.
Keywords: Psychobiology,Bệnh tâm thần